THE RISE OF ARTIFICIAL INTELLIGENCE IN ADAS AND AUTONOMOUS VEHICLES: PROGRESS AND CHALLENGES - Anushree Nagvekar, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the transformative integration of Artificial Intelligence in Advanced Driver Assistance Systems (ADAS) and autonomous vehicles, examining the technological progress, challenges, and future implications for the automotive industry. The article analyzes various aspects including AI-powered ADAS implementations, autonomous vehicle architectures, technical implementations through different machine learning approaches, and critical challenges in widespread deployment. The article encompasses detailed evaluations of key technologies such as Lane Keeping Assist, Adaptive Cruise Control, and Emergency Braking systems, while also addressing data quality concerns, regulatory frameworks, ethical considerations, and complex driving environments. The article highlights significant advancements in AI capabilities while acknowledging persistent challenges in achieving full autonomy, emphasizing the need for continued development in both technological and regulatory domains.